A Transitivity Processes Analysis in Senior High School Textbook Entitled “English for Change” of Merdeka Curriculum - Khasanah, Isma Nur; Candraloka, Olyvia Revalita (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
This study conducts a transitivity analysis of reading texts in the “English for Change” textbook to examine the linguistic characteristics of Indonesian English language teaching materials. Using Halliday’s Systematic Functional Linguistics Framework, the author analyzes 23 reading passage to identify and classify the type of process, participants, and circumstances employed throughout textbook. The objective study to shows the most dominant transitivity system and explore their pedagogical implication in the educational context. The finding reveals that material process are most frequently, actor and goal as the primary actors in participants, accompanied by location and time that provide contextual for language use. The deliberate transitivity choices highlight efforts to build students’ English proficiency while keeping lessons grounded in their sociocultural context. These data, confirm the value of transitivity analysis for evaluating English teaching materials and provide insights for developing future resource, both linguistically appropriate and pedagogically effective.